Mucus Microrheology Measured on Human Bronchial Epithelium Culture - Jory, Myriam; Bellouma, Karim; Blanc, Christophe; Casanellas, Laura; Petit, Aurélie; Reynaud, Paul; Vernisse, Charlotte; Vachier, Isabelle; Bourdin, Arnaud; Massiera, Gladys (Frontiers in Physics, 2019)
We describe an original method to measure mucus microrheology on human bronchial epithelium culture using optical tweezers. We probed rheology on the whole thickness of mucus above the epithelium and showed that mucus gradually varies in rheological response, from an elastic behavior close to the epithelium to a viscous one far away. Microrheology was also performed on mucus collected on the culture, on ex vivo mucus collected by bronchoscopy, and on another epithelium model. Differences are discussed and are related to mucus heterogeneity, adhesiveness and collection method.